Communal Accounting in Minangkabau Culture: An Ethno-Cultural Study of Badantam Practices - Fitri Yulianis; Peregki Susanto; Abror; Nurul Asma Akmal; Erniwati (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study examines the practice of Badantam, a tradition of financial mutual aid in Minangkabau wedding ceremonies, particularly in Nagari Ketaping, Padang Pariaman Regency. This tradition functions not only as a mechanism for pooling funds but also reflects the principles of customary-based accounting implemented simply yet imbued with cultural values. The primary focus of this research is to explore the accounting system used in Badantam, specifically a cash-basis system, in which recording occurs only for transactions received in cash or cash equivalents at the time of the event. A qualitative approach with ethnographic methods was employed. Data were collected through in-depth interviews, participant observation, and documentation, involving informants such as customary leaders, religious figures, community leaders, the wedding organizing family, and surrounding community members. Data analysis followed the interactive model of Miles, Huberman, and Saldana, while data validity was ensured through triangulation of sources, techniques, and time. The findings indicate that Badantam operates through four main stages: collection, recording, announcement, and supervision. During the recording stage, all contributions— whether cash or gold converted to cash value—are formally documented in a special ledger according to sequence and kinship category. This demonstrates the practical application of cash-basis accounting, where recognition occurs only upon actual receipt of funds. Furthermore, transparency is ensured through public announcement of each contribution via loudspeaker; accountability is reflected in clear reporting accessible to all; and supervision is implemented collectively by both the committee and community through direct verification of records and physical cash.This, Badantam can be viewed as an embodiment of cultural accounting, integrating cash-basis principles with the values of transparency, accountability, and collective oversight. This tradition demonstrates that modern accounting principles have long been embedded in Minangkabau customary systems, grounded in local wisdom, social solidarity, and internalized religious values. Keywords: Badantam, Communal Accounting, Minangkabau Culture